Sea‐level rise drives wastewater leakage to coastal waters and storm drains. Issue 3 (25th February 2021) - McKenzie, Trista; Habel, Shellie; Dulai, Henrietta
Abstract: Sea‐level rise (SLR) is expected to compromise coastal wastewater infrastructure (WIS) via groundwater inundation (GWI). We conducted a field‐based study in urban Honolulu, Hawai'i using spring tides as a proxy for future sea levels to quantify the hydrologic connection of WIS. This study focused on two possible pathways: (1) direct GWI of WIS and subsequent discharge into the coastal ocean and (2) indirect inundation of WIS evidenced in storm drains. We used geochemical tracers and emerging organic contaminants (EOCs) to monitor groundwater discharge and its wastewater content. Groundwater discharge and EOCs fluctuated with tides for coastal and canal groundwater and surface water samples, and storm drains, indicating tidally driven GWI and wastewater discharge. This study presents some of the first field‐based evidence for GWI of coastal WIS and demonstrates that SLR is creating additional risks to environmental and human health.